Case report: Severe hypertension-induced priapism in an infant with unrecognized autosomal recessive polycystic kidney disease - Konopásek, Patrik; Ptáčníková, Natálie; Toni, Ledjona; Zieg, Jakub (Frontiers in Pediatrics, 2023)
Priapism is a urologic emergency requiring prompt management. There are three types of priapism: stuttering (intermittent), nonischemic (high flow/arterial) and ischemic (low flow/veno-occlusive). Here, we present the first case of an infant with recurrent nonischemic priapism as a first sign of severe hypertension. An elevenmonth-old infant was admitted for high-flow priapism. During the admission, he was found to have severe hypertension which required the combination of five antihypertensive drugs; abdominal ultrasound showed polycystic kidneys, splenomegaly and a parenchymal liver lesion. The priapism resolved spontaneously and never occurred again after the initiation of antihypertensive treatment. Genetic analysis confirmed autosomal recessive polycystic kidney disease (ARPKD). We found no other explanation for priapism, like genital trauma, hematologic disease or other. Decreased nitrite oxide (NO) bioavailability seen in patients with hypertension seems to be the principal mechanism of the hypertension causing the priapism. This hypothesis is supported by animal models of genetically modified mice lacking nitric oxide synthase. The same mechanism is thought to be the genesis for priapism and other complications like pulmonary hypertension in patients with sickle cell disease.We present a case of severe hypertension-associated priapism in a child with unrecognized ARPKD. The endothelial dysfunction with decreased NO bioavailability seen in patients with hypertension might be the principal pathogenic mechanism.